Optimalisasi Keterampilan Proses Sains pada Analisis Titrimetri dan Gravimetri bagi Peserta Didik SMK Negeri 8 Kota Jayapura - Lusia Narsia Amsad; Jukwati; Frans Deminggus; Rahmat Nurohman; Celine D Sawaki (J-Abdimas Cenderawasih, 2025)
The gap between theory and laboratory practice often presents a major obstacle in vocational education, particularly within the industrial chemistry competency. This community service initiative was established to bridge this disparity by strengthening the Science Process Skills (SPS) of students at SMK Negeri 8 Jayapura through technical training in Titrimetric and Gravimetric analysis. The implementation method adopted an experiential learning approach, encompassing conceptual presentations, interactive discussions, and direct experimentation. This intervention was designed to cultivate skills in observation, precision measurement, and data interpretation. Evaluation results demonstrated a significant surge in cognitive competence, marked by a 32.3% increase in average test scores. In the psychomotor domain, the majority of students were able to demonstrate analysis techniques with high precision (error <3%). These findings indicate that intensive supervision with an adequate instructor-to-student ratio is effective in building standardized laboratory competencies.